1995
DOI: 10.1016/0030-4018(95)00172-5
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and manipulation of atoms using short laser pulses

Abstract: The force resulting from a position-dependent sequence of interactions with short counter-propagating n--pulses of laser radiation can propel atoms towards the small region where the pulses overlap. The optical trap thus formed may be combined with Doppler-cooling laser beams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 16 publications
0
44
0
2
Order By: Relevance
“…A series of identical π pulses that propagate in alternating directions can confine a cloud of atoms, or accelerate them efficiently [21][22][23]. The essence of this scheme is the absorption of a photon from one beam and emission into the counterpropagating one with the 2hk momentum transfer that accompanies the process.…”
Section: B Acceleration Of Atoms and Dephasing On The Excited-state mentioning
confidence: 99%
See 1 more Smart Citation
“…A series of identical π pulses that propagate in alternating directions can confine a cloud of atoms, or accelerate them efficiently [21][22][23]. The essence of this scheme is the absorption of a photon from one beam and emission into the counterpropagating one with the 2hk momentum transfer that accompanies the process.…”
Section: B Acceleration Of Atoms and Dephasing On The Excited-state mentioning
confidence: 99%
“…Excitation on the D 1 line yields an even shorter τ deph . Of course using 5-10 ps pulses does make it possible to accelerate the atoms by repeated action of π pulses similar to [21,23]-at the expense of ground-state selectivity. The important conclusion here is that when quantum control of atoms with multiple excited-state levels is attempted, limiting time scales may appear that are shorter than τ spont , even in the absence of any collisions or inhomogeneous line-broadening mechanisms.…”
Section: B Acceleration Of Atoms and Dephasing On The Excited-state mentioning
confidence: 99%
“…Initially, continuous laser radiation was used for this purpose, but now pulsed laser applications for cooling [4][5][6][7][8][9][10][11] and trapping [12][13][14][15][16] of atoms and molecules are also discussed. In [4] the deceleration of a Na beam by a counterpropagating beam of a mode-locked laser and the appearance of negative velocity atoms were observed for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [12] showed that the force resulting from the interaction of an atom with a sequence of short counterpropagating laser π pulses can propel atoms towards the small region where the pulses overlap, thus counterpropagating sequences of laser pulses may form an optical trap for atoms. In [13] stimulated focusing and deflection of an atomic Cs beam using counterpropagating picosecond laser pulses were * vr@iop.kiev.ua observed that can be treated as experimental justification of the trap idea proposed in [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation